Murdoch mysteries [videorecording (DVD)] : the movies - Outerbridge, Peter; Hawes, Keeley, 1976-; Meaney, Colm, 1953-; Jennings, Maureen (Acorn Media, 2015)
Before the hit television series, the same characters appeared in three feature-length adaptations of Maureen Jennings's beloved novels. In gritty 1890s Toronto, Detective William Murdoch uses new forensic techniques to solve the murders of a young chambermaid, a colleague on the force, and a backstreet abortionist.